GENDER DIFFERENCES IN CLINICAL OUTCOMES AMONG STEMI PATIENTS UNDERGOING PRIMARY PCI - AKBER , S; ABDULLAH, .; KHAN , FR (Biological and Clinical Sciences Research Journal, 2024)
ST-elevation myocardial infarction (STEMI) is a major cause of death worldwide. Primary percutaneous coronary intervention (PCI) is the preferred treatment, restoring coronary blood flow to reduce mortality. However, women often experience worse outcomes after STEMI compared to men. Objective: This study aimed to assess gender differences in clinical outcomes, focusing on in-hospital mortality and heart failure among STEMI patients undergoing primary PCI. Methods: A prospective study was conducted at Lady Reading Hospital Peshawar from January to July 2020. The study included 298 STEMI patients aged 35-70 years who underwent primary PCI. Of these, 154 were females (51.7%) and 144 were males (48.3%). Data on demographics, clinical features, and outcomes were collected. Statistical analysis was performed using SPSS Version 25. Continuous variables were presented as mean ± standard deviation, and categorical variables as percentages. Multivariate logistic regression was applied to control for confounding factors. Results: Female patients showed a higher rate of heart failure (12.8% vs. 6.1%, p=0.011) and in-hospital mortality (7.0% vs. 3.5%, p=0.020) compared to males. The odds ratio for heart failure in females was 0.389 (95% CI 0.185-0.817), and for mortality, it was 0.310 (95% CI 0.111-0.870). Stent thrombosis rates were similar between genders (1.7% each, p=0.707). Major bleeding was more frequent in females (2.3% vs. 1.4%), though the difference was not significant (p=0.770).Conclusion: This study reveals significant gender disparities in STEMI outcomes after primary PCI, with women at greater risk for heart failure and in-hospital mortality. These findings highlight the need for tailored strategies in STEMI management to improve outcomes for women.